The "State" of the Arctic - Finger, Matthias (2011)
Professor Matthias Finger, EPFL - the Ecole Polytechnique Fédérale de Lausanne, Switzerland, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.